An optimal control approach of integrating traffic signals and cooperative vehicle trajectories at intersections. Issue 1 (31st December 2022) - Liu, Meiqi; Zhao, J.; Hoogendoorn, S. P.; Wang, M.
Abstract : An integrated approach for optimising traffic signals and cooperative vehicle trajectories at urban intersections is proposed. The upper layer determines the optimal signals using enumeration and the lower layer optimises trajectories under each feasible signal plan. In the lower layer, platoon accelerations are optimised considering comfort and delay while satisfying motion constraints and safe requirements. The red phase is enforced as a logic constraint, which restricts vehicles to stay behind the stop-line. Typical platoon manoeuvres such as split and approach can be included in the lower layer. The integrated control approach is adaptive to traffic demands and flexible in incorporating different traffic movements during multiple signal phases. The controller performance is verified by simulation of three designed scenarios. The comparison with trajectory optimization and signal optimization demonstrates the advantages on throughput, fuel economy, delay and vehicle stops, and reveals insights into the optimal patterns on signals and trajectories.